Prevention of Illiteracy of the Al-Quran From an Early Age - Zulham Effendi; Said Hidayat; Rozaanah Rozaanah (As-sunnah: Jurnal Pengabdian Masyarakat, 2022)
Being able to read the Quran is a standard that every Muslim cannot but have. This is because all forms of worship, both mandatory and sunnah, must contain the readings of the Quran, ranging from the five-time mandatory prayer to the hajj which is performed only for able Muslims. But with the development of the times and the busyness of human beings, this thing that should be very important is often forgotten and underestimated by Muslims. As a result, it is starting to be seen in the present, many children are more encouraged by their parents for math lessons, and piano lessons, than to learn to read the Quran. So in the author's monitoring through interviews and observations carried out at the location of community service activities, it can be seen that more than 80% of children over 10 years old have not been able to read the Quran at all. This research uses a qualitative point of view where data is taken, processed, and presented in a non-numerical form so that complex problems can be seen and solved with real actions in several cycles. After taking action on the problems that occurred at the community service location, the author found significant progress, as can be seen from the enthusiasm of parents in taking their children to participate in tahsin activities at community service locations. The development of participants was very rapid even though the time for carrying out the activity was relatively narrow, the average child who participated in this activity could already read simple fragments from verses from the Quran. There are even some children who have memorized several short letters in that short time. Tahsin's activities, which were carried out as an effort to prevent illiteracy of the Quran at the community service location, went smoothly and each cycle was completed properly even though the implementation time was not enough to achieve perfect results. This can be applied by other researchers in similar community service activities elsewhere so that concerns about illiteracy in the Quran can be overcome and addressed together.